Plasticidade ornamental e propagação de herbáceas para utilização em telhado verde - Barosky, Taciane Kunst (2011)
In times of search for sustainability, the green roof is an alternative that is attracting increasing attention. Define themselves as green roof, a vegetation cover on the roof of buildings, the advantages of this technique are many, for example, thermal comfort and reducing pollution, reducing the visual impact of buildings. In Brazil, through tax incentives and benefits provided by some municipalities, the adoption of this technique has gained emphasis. However, current data are lacking in information in relation to plant species that can be used in green roof technology. In this sense, the problem is rooted in the lack of specific knowledge about the plasticity and ecological ornamental plant species in the use of green roof technology. The objective of this work is to provide knowledge on species with herbaceous ornamental and ecological plasticity, the technology being used in green roofs in urbanized environment. This survey was distributed in three experiments, plasticity and propagation of ornamental grass for use in green roof; Propagation of Aspilia montevidensis (Spreng.) Kuntze (Asteraceae) by the process of cutting and vegetative propagation and growth of two herbaceous species succulent, with and without the use of shade cloth. The green roof technology ecotelhado ® proved to be more efficient and kind Aspilia montevidensis for being too rough can be nominated for this technology. The users will make the process of vegetative propagation by cuttings in the spring for the species Aspilia montevidensis without the use of IBA, leaving four leaves at the stake. The species Callisia repens (Jacq.) Sedum acre L. and L, may be indicated for use in green roof technology between the months March and May